تطهير المصارف الإسلامية من المال الحرام (الأموال المجنبة) مملكة البحرين نموذجا - درويش، عبد الحميد ابرهيم (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2021)
This study “purifying Islamic banks from prohibited funds” (provisioned funds) Kingdom of Bahrain as a model. The study aimed to know the reality of funds that Islamic banks provision for purification and how it is used in legitimate ways. The problem in this study is to present the obstacles that Islamic banks face when utilize their funds that are provisional for purification, then finding solutions that will help in that. The questions of the study were to know the reality of the provisional funds for purification, and the standards that are used by the Islamic banks for that, as well as the extent of their suitability to Islamic laws, and finding alternatives to the standards that conflict with it, in addition to several goals that answer these questions. The researcher followed the inductive approach for the purpose of tracing the scientific material from the heritage of Islamic jurisprudence in the past and present, as well as the descriptive, analytical, and critical approach in order to get the widest details possible for this study. This study consists of five chapters, the first one presents the introductory framework, the second chapter is an introduction to Islamic Banks in Kingdom of Bahrain, then the third chapter about the reality of provisional funds for purification and its reasons, and the fourth chapter about the laws of those funds in Islamic Jurisprudence, followed by the fifth chapter about pursuance of Islamic banks in purification of their funds. to conclude with a number of recommendations and proposals that will play an important role in this field if applied.